Reinvention sewing with rescued materials - Donenfeld, Maya (John Wiley & Sons, 2012)
Presents a guide to working with recycled materials such as linen, burlap and wool. Shows 28 projects with deconstruction techniques, sewing tips and information about their environmental impact. Projects include totes, lunch sack, scarf, onion sack, skirt, bin and many more--Source other than Library of Congress.